Bicycle station facilities preferences of bike riders in a Malaysian public university - Vosoughi, Shirin (2015)
Universally, the community of scientists agrees that there are adverse global climate changes caused by industrialization and ever-increasing use of fossil fuel. In progressive nations, think tanks have focused on devising ways of “green” and “sustainable” lifestyles, to reduce usage of fossil fuel and related emission of carbon and other pollutants. A major contributor to air pollution is auto emissions especially in crowded major cities. During the recent decade, many progressive cities have successfully encouraged and facilitated using bicycles as a viable, clean mode of transportation. Hence, this study aims to understand bike riders’ preference of bicycle station facilities in Universiti Putra Malaysia (UPM) Serdang campus. In addition, it purposes to encourage students to use bicycles as a mode of transportation. The criteria of identifying factors influencing the cyclist preferences on designing a bicycle station and determining UPM students’ preferences regarding bicycle station facilities and its design in Serdang campus, and also recommending ways to enhance the design of a bicycle station in UPM Serdang campus is studied. Achieving these objectives was done by designing functional and aesthetically attractive “bicycle stations”, to be built on dedicated bicycle paths. The study instrument was based on a survey taken from 327 students and staffs of UPM who had bicycles, or used bicycles on campus. Their preference on the type of facilities in bicycle stations was solicited. This study revealed that bike riders are willing to use bicycles as a mode choice, if their need and preference provided. There should be shelter stations, lockdown stations and a main bicycle station with essential facilities. Also the motorized vehicles should be banned from entering campus area (except for taxis, minibuses and campus buses). It is advised to reward those students who use bicycles or other non-polluting transportation systems to have a superior hostel room condition. Safety is the most important priority and advertising is essential to promote cycling.